ANALISIS FAKTOR KENDALA DAN KELAYAKAN USAHA BATIK BANYUMAS - Wulandari, Siti Zulaikha; Novandari, Weni (Faculty of Economics and Business Universitas Jenderal Soedirman, 2008)
Batik is generally thought of as the most unique Indonesian fashion. They produced from several regions, especially Central Java (including Banyumas) and Jogjakarta as the center of the art. Since 1970’s, the golden era of Batik Banyumas has gone. The number of people in Banyumas who rely on Batik for their living decreasing significantly from day to day. There is a worried that Batik Banyumas as the most distinctive heritage will disappear. This reseach is designed to find out some inhibitant factors perceived by business people in developing Batik Banyumas using Analytical Hierarch Process (AHP). Moreover, case study is conducted to calculate the feasibility of investing in printing batik from marketing and financial aspects